An empirical analysis of the usefulness of the Basel II Pillar 3 disclosures on bank risk management to monitor bank performance and forecast bank profitability during periods of economic instability : a thesis presented in partial fulfilment of the requirements for the degree of Master of Management in Banking at Massey University, Manawatu, New Zealand - Ainsworth, Rachel (Massey University, 2012)
The third pillar of the Basel II capital adequacy framework requires banks to disclose risk information to the market to supplement regulators’ monitoring. It is expected that this “allows market discipline to work earlier and more effectively” (BCBS, 1998, pp. 6). The expectation that the pillar 3 disclosures will lead to market discipline is supported in the theoretical literature but not demonstrated in the empirical literature. The purpose of this thesis is to determine if the information contained in banks’ disclosures is useful to monitor bank performance and to explain bank profitability as this is a precondition for effective market disclosure. The usefulness of information in the pillar 3 disclosures was examined for twenty of the largest global banks from 2008 and 2009. It was found that pillar 3 disclosures are useful to analyse and monitor the performance of banks as the disclosures can be used to identify banks for which key risk metrics are inconsistent with other metrics. The pillar 3 variables did not however significantly improve the explanatory ability of earnings models over models containing only financial information, although this may be due to the small sample size. These results show that there is valuable information contained within pillar 3 disclosures which could be used by the market to provide market discipline as expected in the Basel II framework.
Keywords: Basel II (2004); Banking; Risk management; Disclosure (Accounting)